Breathlessness and exercise with virtual reality system in long-post-coronavirus disease 2019 patients - Stavrou, Vasileios T.; Vavougios, George D.; Kalogiannis, Periklis; Tachoulas, Konstantinos; Touloudi, Evlalia; Astara, Kyriaki; Mysiris, Dimitrios S.; Tsirimona, Glykeria; Papayianni, Eirini; Boutlas, Stylianos; Hassandra, Mary; Daniil, Zoe; et al. (Frontiers in Public Health, 2023)
Long-post-coronavirus disease-2019 (COVID-19) patients tend to claim residual symptomatology from various systems, most importantly the respiratory and central nervous systems. Breathlessness and brain fog are the main complaints. The pulmonary function pattern is consistent with restrictive defects, which, in most cases, are self-resolved, while the cognitive profile may be impaired. Rehabilitation is an ongoing field for holistic management of long-post-COVID-19 patients. Virtual reality (VR) applications may represent an innovative implementation of rehabilitation. We aimed to investigate the effect of exercise with and without the VR system and to assess further breathlessness and functional fitness indicators in long-post-COVID-19 patients with mild cognitive impairment after self-selected exercise duration using the VR system. Twenty long-post-COVID-19 patients were enrolled in our study (age: 53.9 ± 9.1 years, male: 80%, body mass index: 28.1 ± 3.1 kg/m2). Participants' anthropometric data were recorded, and they underwent pulmonary functional test evaluation as well as sleep quality and cognitive assessment. The participants randomly exercised with and without a VR system (VR vs. no-VR) and, later, self-selected the exercise duration using the VR system. The results showed that exercise with VR resulted in a lower dyspnea score than exercise without VR. In conclusion, VR applications seem to be an attractive and safe tool for implementing rehabilitation. They can enhance performance during exercise and benefit patients with both respiratory and cognitive symptoms.